2020
DOI: 10.1021/acs.analchem.0c01956
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Interface for Enabling Spectroelectrochemical Investigations in Evanescent-Wave Cavity-Ring-Down Spectroscopy

Abstract: In this study, we report the development of an electrically active solid−liquid interface for the evanescent-wave cavity-ring-down spectroscopic (EW-CRDS) technique to enable spectroelectrochemical investigations of redox events. Because of a high-quality transparent conductive electrode film of indium tin oxide (ITO) coated on the interface of total internal reflection of the EW-CRDS platform, a cavity ring-down time of about 900 ns was obtained allowing spectroelectrochemical studies at solid− liquid interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Also, the lowest binding affinity of Cyt-C was observed when the EA-IOW was functionalized with APTES, presumably due to the electrostatic repulsion between Cyt-C and APTES, which both have overall positive charges at neutral pH 44,45 . When compared to ITO/APTES interface a clear increase in the equilibrium constant for the bare ITO is seen, this may be attributed to the favorable adsorption based on the electrostatic attraction between positively charged amino acid residues (lysine) and the −OH groups of ITO; these results are agree well with reported work of Cyt-C adsorption onto ITO surface 39,46 . In Table 1 it is also noticed that the Ab in combination with the ProG species show a higher equilibrium, which indicates that most likely the ProG indeed works to properly orient the capturing Ab for efficient binding of analyte 47,48 .…”
Section: Iii(b))supporting
confidence: 89%
“…Also, the lowest binding affinity of Cyt-C was observed when the EA-IOW was functionalized with APTES, presumably due to the electrostatic repulsion between Cyt-C and APTES, which both have overall positive charges at neutral pH 44,45 . When compared to ITO/APTES interface a clear increase in the equilibrium constant for the bare ITO is seen, this may be attributed to the favorable adsorption based on the electrostatic attraction between positively charged amino acid residues (lysine) and the −OH groups of ITO; these results are agree well with reported work of Cyt-C adsorption onto ITO surface 39,46 . In Table 1 it is also noticed that the Ab in combination with the ProG species show a higher equilibrium, which indicates that most likely the ProG indeed works to properly orient the capturing Ab for efficient binding of analyte 47,48 .…”
Section: Iii(b))supporting
confidence: 89%
“…This indicated that bi-sources of Zn and the ligand aided in the construction of more defective interfaces in C-ZnO 0.5 /ZAA foam, which was shown to have a high redox ability when compared to pure ZnO and ZIF-8. 103,104 Based on the above photo-electric performance analysis, C-ZnO 0.5 /ZAA foam had enhanced photo-absorption, photo-induced electrons, conductivity, and redox ability, endowing C-ZnO 0.5 /ZAA foam with efficient photocatalysis-assisted regeneration.…”
Section: Characterization Of Interfacial Charge Transfermentioning
confidence: 99%
“…Copyright 2020 American Chemical Society. (b) Reproduced from Alnaanah, S. A.; Roussel, T. J., Jr.; Ghithan, J. H.; Qatamin, A. H.; Irziqat, M. A.; Telfah, H.; Liu, J.; Mendes, S. B. Analytical Chemistry 2020 , 92 (16), 11288–11296 (ref ). Copyright 2020 American Chemical Society.…”
Section: Optical Cavity-based Hybrid Techniquesmentioning
confidence: 99%
“…They reported a minimum detection limit of 1.2 pM for the detection of a mutated gene associated with sickle-cell anemia. However, Alnaanah et al, 111 in a recent study, demonstrated a unique electrically active EW-CRDS platform to investigate the spectroelectrochemical redox events (Figure 9b). They coated the TIR surface of a rightangled NBK-7 prism with an electroactive and highly transparent indium tin oxide (ITO) film of thickness about 13 nm.…”
mentioning
confidence: 99%